Yield, Growth, Quality, Biochemical Characteristics and Elemental Composition of Plant Parts of Celery Leafy, Stalk and Root Types Grown in the Northern Hemisphere - Nadezhda A. Golubkina; Viktor A. Kharchenko; Anastasia I. Moldovan; Andrey A. Koshevarov; Svetlana Zamana; Sergey Nadezhkin; Alexey Soldatenko; Agnieszka Sekara; Alessio Tallarita; Gianluca Caruso (Plants, 2020)
Celery is one of the major nutraceutical vegetable species due to the high dietary and medicinal properties of all of its plant parts. Yield, growth and produce quality of six celery genotypes belonging to leafy (Elixir and Samurai), stalk (Atlant and Primus) or root (Egor and Dobrynya) types, as well as the distribution of biomass, sugars, mineral elements and antioxidants among the different plant parts, were assessed. Within the celery root type, cultivar Dobrynya resulted in higher yield than Egor, whereas the genotype did not significantly affect the marketable plant part production of leafy and stalk types. Leaf/petiole ratios relevant to biomass, total dissolved solids, sugars, ascorbic acid, flavonoids, antioxidant activity and ash, K, Zn, Fe, Mn, Cu and Se content were significantly affected by the celery type examined. Ash content was highest in the leaves and lowest in the roots. Celery antioxidant system was characterized by highly significant relationships between ascorbic acid, polyphenols, flavonoids, antioxidant activity and Zn. Among the celery types analyzed, the highest values of chlorophyll, Fe and Mn content as well as antioxidant activity were recorded in leaves from root genotypes, which suggests interesting nutraceutical prospects of the aforementioned plant parts for human utilization.